A Rare Case of Chryseobacterium Indolegens Bacteremia in A PretermInfant In A Tertiary Care Hospital In Bangalore - S Manasa; Sagar Sharma H.S (Pediatric Review: International Journal of Pediatric Research, 2022)
Multi-drug resistant organisms are very common worldwide. Bloodstream infection byChryseobacterium indologenes is one of the healthcare-associated infections which is resistant tomost antibiotics. It is usually seen in preterms, patients on immunosuppressive drugs or havingmalignancy and patients with indwelling devices. It causes various types of infections, such asbacteremia, pneumonia, meningitis, and artificial shunt infection, especially with harbouring invasivedevices and indwelling catheters. Management of C.indologenes in neonates is not adequatelydocumented leading to under-reporting in India. In our hospital, we had a preterm baby of 31 weeksweighing 1.36kg, who presented with respiratory distress syndrome with an umbilical veincatheterization with signs of sepsis. The blood culture yielded C.indologenes with resistance to mostof the group of antibiotics.